Participação das células Th1, Th17 e T reguladoras no desenvolvimento da tu-berculose ativa - SILVA, Bruna Daniella de Souza (2010)
Tuberculosis (TB) is a disease that afflicts mankind catastrophically, causing millions of new cases and deaths worldwide. It is estimated that one third of the world population is infected with the TB bacillus, Mycobacterium tuberculosis. Currently, the major challenges in TB control are the iden-tification of latent individuals, who are have increased chances to become ill, and the effective treat-ment of individuals with active disease. Understanding the immunology of this disease is of crucial importance for the development of new diagnostic tests and vaccines to combat this disease effec-tively. In order to elucidate the cellular immune response in tuberculosis, we evaluated the subpopu-lations of TCD4+ Th1, Th17 and T regulatory cells of patients with active pulmonary tuberculosis and rheumatoid arthritis against the recombinant antigen GLcB of M. tuberculosis. Peripheral blood mononuclear cells were obtained from twenty one patients with active pulmonary tuberculosis, re-cruited at Anuar Auad Hospital, twenty five patients with rheumatoid arthritis (RA), eleven individu-als with latent tuberculosis (TST+) and twelve healthy subjects (TST-). These cells were cultured, stimulated with antigen recombinant GLcB and Th1, Th17 and T regulatory subsets cells were eva-luated by flow cytometry. It was found that patients with active pulmonary tuberculosis have a high-er response of Th1 (8.21.9), Th17 (3.92.1) and T regulatory (2.81.2) antigen-specific recombi-nant GLcB when compared with individuals with latent infection (Th17=2.81.3; Treg=3.11.2) and healthy controls (Th17=1.40.8; Treg=0.60.3). Individuals with latent infection have only a signifi-cant percentage of Th1 cells specific (4.61.1) to GLcB when compared to controls (1.71.0). RA Patients that developed tuberculosis had immune response similar to those with only TB. Given these results, we conclude that the Th1 cells, Th17 and regulatory T cells are directly involved in active disease.